2021
DOI: 10.1038/s41588-020-00771-1
|View full text |Cite|
|
Sign up to set email alerts
|

Mutation load at a mimicry supergene sheds new light on the evolution of inversion polymorphisms

Abstract: Chromosomal inversions are ubiquitous in genomes and often coordinate complex phenotypes, such as the covariation of behavior and morphology in many birds, fishes, insects or mammals [1][2][3][4][5][6][7][8][9][10][11] . However, why and how inversions become associated with polymorphic traits remains obscure. Here we show that despite a strong selective advantage when they form, inversions accumulate recessive deleterious mutations that generate frequency-dependent selection and promote their maintenance at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
189
2
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(234 citation statements)
references
References 72 publications
14
189
2
6
Order By: Relevance
“…Furthermore, Jay et al (2021) found that the inversions P 1 , P 2 , and P 3 show an elevated proportion of nonsynonymous relative to synonymous polymorphism ( p N /p S ) in comparison to genome-wide estimates and estimates for noninverted homologous regions. Interestingly, experiments have shown strongly reduced larval survivorship of individuals homozygous for the same derived inverted arrangement at the supergene ( Jay et al 2021 ). Thus, the accumulation of mutations in H. numata may also contribute to maintenance of the supergene polymorphism, as heterozygotes for alternative recessive deleterious mutations are fitter than homozygotes.…”
Section: Genomic Architectures Of Supergenes: Implications For Evolutionary Trajectoriesmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, Jay et al (2021) found that the inversions P 1 , P 2 , and P 3 show an elevated proportion of nonsynonymous relative to synonymous polymorphism ( p N /p S ) in comparison to genome-wide estimates and estimates for noninverted homologous regions. Interestingly, experiments have shown strongly reduced larval survivorship of individuals homozygous for the same derived inverted arrangement at the supergene ( Jay et al 2021 ). Thus, the accumulation of mutations in H. numata may also contribute to maintenance of the supergene polymorphism, as heterozygotes for alternative recessive deleterious mutations are fitter than homozygotes.…”
Section: Genomic Architectures Of Supergenes: Implications For Evolutionary Trajectoriesmentioning
confidence: 97%
“…Initial genetic work determined that the complex mimicry polymorphism in H. numata is governed by the P locus, a genomic region that harbors a set of genomic rearrangements that guarantee the joint inheritance of loci involved in color patterning due to the presence of a 400-kb inversion (P 1 ) containing 21 genes ( Joron et al 2006 , 2011 ; Jay et al 2021 ). The P 1 inversion includes cortex , a gene involved in pigmentation patterning in many butterfly lineages ( Nadeau et al 2016 ).…”
Section: Genomic Architectures Of Supergenes: Implications For Evolutionary Trajectoriesmentioning
confidence: 99%
See 3 more Smart Citations